Diagnostic Accuracy of MRI in Detecting Stromal Invasion in Early Cervical Cancer Patients Taking Histopathology as Gold Standard: Detecting Stromal Invasion in Cervical Cancer - Ahmad, Nosheen; Mukhtar, Maryum; Gilani, Aamna; Bukhari, Adeela Abid; Manzoor, Amber; Liaqat, Ayesha (Pakistan Journal of Health Sciences, 2025)
Cervical cancer is a major cause of cancer-related deaths among women. MRI is a non- invasive imaging technique commonly used to evaluate tumor extent, but its diagnostic accuracy in detecting stromal invasion in early cervical cancer remains uncertain. Objective: To determine the diagnostic accuracy of MRI in detecting stromal invasion in early cervical cancer patients taking histopathology as gold standard. Methods: This Cross-sectional validation was conducted at the Department of Radiology, Faisalabad Medical University (FMU), Faisalabad, form 1st April 2024 to 30th September 2024. A total of 200 patients aged 30-70 years with early cervical cancer were included in the study. All patients underwent pelvic MRI scans using a 1.5 Tesla MRI machine. The MRI findings were assessed for the presence or absence of stromal invasion and compared with histopathology results. All the data was analyzed in SPSS and sensitivity, specificity, and diagnostic accuracy was calculated for MRI against histopathology. Results: The overall sensitivity, specificity, Positive Predictive Value (PPV), negative predictive value (NPV), and diagnostic accuracy of MRI in detecting stromal invasion in early cervical cancer patients, were 91.26%, 89.70%, 90.38%, 90.63%, and 90.50%, respectively with histopathology as the gold standard. Conclusion: This study concluded that MRI has a high diagnostic accuracy in detecting stromal invasion in early cervical cancer patients.